Pemodelan Sistem Dinamik Eco-Drainage di Wilayah Tanah Basah (Studi Kasus Kawasan Kelapa Gading DKI Jakarta) - Rahmawati Fitria; Henita Rahmayanti; Bagus Sumargo (Rekayasa, 2022)
An Ecological drainage becomes an application in this development project in the Kelapa Gading area. The drainage concept that is applied is a drainage system in which rainwater that falls on road surface runoff will flow directly into the water infiltration system and directly fill the ground surface water. Geologically, it can be seen that North Jakarta is an area with a fairly high ground water level (MAT), and has an average MAT elevation of 2 - 2.5 m. This study intends to determine the ability of this ecodrainage to reduce runoff/floods that often occur in areas with a fairly high MAL. What direct benefits can be felt in the use of ecodrainage in these flood-prone areas, thus making the basic reason for applying this ecodrainage. This study uses a dynamic systems approach. In the preparation of the dynamic system model, Powersim Studio Version 10 software will be assisted. The simulation results show that an increase in rainfall every year will provide an increasing flood potential. By using eco-drainage, it is felt that it is not optimal enough to reduce runoff in areas that have high MAT levels. However, this ecodrainage still provides broad sustainability benefits. The quantity of groundwater will slowly be filled up to the aquier layer through this ecodrainage. This step is considered to be able to help prevent the aquifer layer from being exposed and have an impact on the rate of land subsidence so that the potential for flooding will decrease.